2022
DOI: 10.32872/cpe.5533
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the outcome of expressive writing in parents of children with leukaemia

Abstract: Background Sex differences are widely reported in clinical psychology but are rarely examined in interventions. Method This mixed-method explorative study examined sex differences in 13 mothers and 10 fathers of children in the off-therapy phase of acute lymphoblastic leukaemia. Parents underwent an expressive writing intervention using the guided written disclosure protocol (GWDP). Results Mothers had more nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The researchers concluded that since written expression is a non-invasive and cost-effective intervention, it can be used in conjunction with primary treatments to improve the sexual performance of women with MS [18]. Interestingly, according to the study by Christiansen et al (2022), the difference between male and female gender can in uence the outcomes of written expression intervention [11]. Baikie et al (2018) also demonstrated that individual differences and the level of basic physical and mental health can have an impact on the effectiveness of written expression in various research communities [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that since written expression is a non-invasive and cost-effective intervention, it can be used in conjunction with primary treatments to improve the sexual performance of women with MS [18]. Interestingly, according to the study by Christiansen et al (2022), the difference between male and female gender can in uence the outcomes of written expression intervention [11]. Baikie et al (2018) also demonstrated that individual differences and the level of basic physical and mental health can have an impact on the effectiveness of written expression in various research communities [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in various studies on the intervention of written expression in recent years. It is also possible that the difference between men and women can have an impact on the results [11]. Considering the lack of studies in this eld speci cally focusing on men with MS; this study was conducted to determine the effect of written expression on the sexual self-concept of men with MS.…”
Section: Introductionmentioning
confidence: 99%